Treatment Gains from Early and Intensive Behavioral Intervention (EIBI) are Maintained 10 Years Later. Issue 4 (July 2021) - Smith, Dean P.; Hayward, Diane W.; Gale, Catherine M.; Eikeseth, Svein; Klintwall, Lars
This study reports outcome in adolescents with autism who in their childhood received Early and Intensive Behavioral Intervention (EIBI). Nineteen children (16 boys) who had received two years of EIBI starting at a mean age of 2-years-and-11-months were followed up, on average, 12 years later. Results showed the participants significantly increased their cognitive and adaptive standard scores during the two years of EIBI, and that these gains were maintained at follow-up, 10 years after the EIBI had ended. Participants also showed a significant reduction in autism symptoms between intake and follow-up. At follow-up, none of the participants had received any additional psychiatric diagnoses, and none were taking any psychotropic medication. Results indicate that treatment gains achieved in EIBI are maintained into adolescence.